ISGylation in Innate Antiviral Immunity and Pathogen Defense Responses: A Review - Zhang, Mengdi; Li, Jingxian; Yan, Haiyan; Huang, Jun; Wang, Fangwei; Liu, Ting; Zeng, Linghui; Zhou, Fangfang (Frontiers in Cell and Developmental Biology, 2021)
The interferon-stimulating gene 15 (ISG15) protein is a ubiquitin-like protein induced by interferons or pathogens. ISG15 can exist in free form or covalently bind to the target protein through an enzymatic cascade reaction, which is called ISGylation. ISGylation has been found to play an important role in the innate immune responses induced by type I interferon, and is, thus, critical for the defense of host cells against RNA, DNA, and retroviruses. Through covalent binding with the host and viral target proteins, ISG15 inhibits the release of viral particles, hinder viral replication, and regulates the incubation period of viruses, thereby exerting strong antiviral effects. The SARS-CoV-2 papain-like protease, a virus-encoded deubiquitinating enzyme, has demonstrated activity on both ubiquitin and ISG15 chain conjugations, thus playing a suppressive role against the host antiviral innate immune response. Here we review the recent research progress in understanding ISG15-type ubiquitin-like modifications, with an emphasis on the underlying molecular mechanisms. We provide comprehensive references for further studies on the role of ISG15 in antiviral immunity, which may enable development of new antiviral drugs.